(3GOGA GdhGLH GdhXjai cSHH ddEHGMI (B/ s - (3Ydi SGde Ydi SGde GdfYjeis; (3eCehf eMeO SdGeIs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2005)
(3Gf GSHGH GdGHGMI ceG jaUM YfgG GSegG GMhGd JHOh ajgG GdhGbYI ef MjK GdXGgQ eSJLeYI cd GdYfGUQ GdJi JdRe dGYJHGQgG LQjeI (B: (3hdcfgG eY Pdc dG JYO LQjeI hPdc dhLhO bGYOI bGfhfjI JQNU HGQJcGH GdaYd ai Jdc GdGMhGd Gh JhLjg aGdbGfhf jMfi GdMb ai SdGeI GdHOf (B: (3hdgPG (B: (3agh jLQe GaYGd GdVQH hGdLQM hjYGbH ef jQJcH gPG GdaYd Gh PGc (B: (3dcfI ai GdhbJ PGJg jSeM ddWHjH HeeGQSI egfJg (B: (3hQHeG JWdH GdGeQ Gf jLQi GdWHjH LQGMI deQjV bO JDOi Gdi HJQ YVh ef GYVGFgs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi, (B2005s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B293-302s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3GdGHGMIs; (3GdhGLH GdhXjais; (3bGYOI bGfhfjIs; (3GdCeQ GdTQYj ddQFjSs; (3GdSdWI GdXfjIs; (3GdCeQ GdQFGSj ZjQ GdTQYj s; (3GdJKHJ hGdJMQjs; (3MSf fjI GdehXa GdYGes; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs